EDUKASI KEBUTUHAN GIZI REMAJA PUTRI - Irni Setyawati; Kusniyati Utami; Dian Soekmawaty Riezqy Ariendha; Hardaniyati Hardaniyati; Yesvi Zulfiana; Sarah Husniyati (Jurnal LENTERA, 2022)
The quality of the nation's next generation is largely determined by young women who act as prospective mothers. Data from the Riskesdas report for the NTB province in 2018 reported that the city of Mataram had the second most thin women aged >18 years (14.02%) after North Lombok district, which was 15.99%. An initial survey conducted on 20 female students by accident at STIKes Yarsi Mataram in February 2021 found 30% of female students had Lila <23.5 cm and deliberately limited eating because they did not want to look fat. This situation shows that not all female students at STIKes Yarsi Mataram have good nutritional status and awareness of their nutritional needs. Based on the problems above, community service "Education on the nutritional needs of young women" was carried out. This community service partner is the Chair of STIKes Yarsi Mataram and the Head of the Midwifery Study Program for the Undergraduate Program. This community service uses the counseling method. Education begins with a pre-test and ends with a post-test. The measurement of female students' knowledge level was carried out using a questionnaire. Education is carried out using the question and answer lecture method. Education of the nutritional needs of adolescent girls at STIKes Yarsi Mataram female students was able to increase female students' knowledge about the understanding and principles of balanced nutrition guidelines and the recommended amount of energy and protein adequacy portions from 76.7% with sufficient knowledge to 76.7% with good knowledge. It is expected that female students can update information related to energy and protein needs in adolescent girls and apply a diet in accordance with the recommended amount of energy and protein adequacy that has been understood.